PENGARUH FRAKSI AKTIF KULIT BATANG DYSOXYLUM ACUTANGULUM MIQ. (MELIACEAE) TERHADAP REPRODUKSI CROCIDOLOMIA PAVONANA (F.) (LEPIDOPTERA: PYRALIDAE) - Edy Syahputra, Djoko Prijono, dan Partomuan Simanjuntak . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Effects of an active fraction of stem bark of Dysoxylum acutangulum Miq. (Meliaceae) on reproduction of Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae).  This study was conducted to determine the effect of an active fraction of Dysoxylum acutangulum stem bark on reproduction and longevity of the cabbage pest Crocidolomia pavonana.  The feeding treatment with the test material was given to the second-instar larvae C. pavonana at concentrations of 2.54, 3.29 and 3.93 ppm (equivalent to LC10, LC30 and LC50), then the emerging adults were observed for their fecundity, ovarial protein content and longevity.  The treatment with the test material at LC50 shortened the lifespan of adult males and females C. pavonana by 2.9 and 1.6 days, respectively, compared with controls.  The treatments at LC10, LC30 and LC50 decreased the fecundity of the adult females by 44.0, 64.7 and 58.1%, respectively, compared with controls, and this effect could be associated with the decrease in protein content of ovaries of the females (29.0, 47.8 and 42.8% decrease, respectively).  Such treatments also delayed the maturity of ovaries of the females.  Suppression of reproductive capacity of C. pavonana could contribute significantly to overall suppression of the pest population if the test material is used in the field.